in vitro Antioxidant Activity of Ethyl Acetate Fraction of Fermentation Products of Ginkgo biloba - Liu, Xuan; Zhan, Xin; Zou, Xianwei; Huang, Yun; Li, Qian; Wang, Jicheng; Xin, Min; Tang, Jintian (Asian Journal of Chemistry, 2014)
We investigated the in vitro antioxidant activity of the ethyl acetate fractions of both fermentation and non-fermentation products of Ginkgo biloba leaves using 2,2-diphenyl-1-picrylhydrazyl and 2,2'-azino-bis(3-ethyl benzothiazoline-6-sulfonic acid) diammonium salt (ABTS•+) assays. Using the two assays, we show that the free radical scavenging activity of the ethyl acetate fraction of 11 days fermentation product was strong on a large range of concentrations (0.800-20.000 mg/mL). Furthermore, using the HPLC and NMR techniques, we discovered for the first time the pharmacodynamic material basis of the in vitro antioxidant effect of G. biloba leaves; namely, caffeine was produced during microbial fermentation of G. biloba by Eurotium cristatum and was present in the ethyl acetate fraction of 11days fermentation product.